The Implication of Indonesia’s IUU Fishing Policy in Natuna Territorial Waters towards South China Sea Geopolitics - Anggraini, Silvia Dian; Kusumawardhana, Indra; Ramadhan, Iqbal (Jurnal Hubungan Internasional, 2018)
The agenda of Jokowi’s administration demands a strong measure to protect maritime security and sovereignty of Indonesia; especially its national sovereignty and maritime security in the vast boundary of Indonesian territorial waters. However, the implementation faces challenges related to violations of sovereignty in the territorial waters. One of them was due to the rampant illegal fishing activities that threaten the sufficiency of the fish stock. Exposed to such threat, Indonesia’s commitment to secure its maritime sovereignty was strongly projected by the emergence of a ‘Sink the Vessels’ policy by the Ministry of Marine Affairs and Fisheries (KKP), chaired by Susi Pudjiastuti since 2014. In the context of the South China Sea polemics which shows the relationship with the territorial waters of Indonesia in Natuna, the policy has significant implication to the South China Sea maritime geopolitics. The question is what the implications of the ‘Sink the Vessels’ policy toward maritime geopolitics in the South China Sea. Using structuration and geopolitics approaches, this article argues that Indonesia’s IUU Fishing policy enhances the complexity of maritime security in the South China Sea which ultimately leads to the strengthening of political realism behaviour among countries whom potential to conflict with Indonesia in the context of IUU Fishing in Natuna waters.